Integration of Religious Moderation in the Framework of Character Education for Discipline and Patriotism in Secondary Schools - Diyati, Turrus; Sa’adi (International Journal on Education Issues, 2025)
Purpose - This study investigates the implementation of the Islamic moderation values (Wasathiyah), specifically discipline (Istiqamah) and patriotism (Hubb al-Watan), at MAN Salatiga via scout programs. The research seeks to describe these values, analyze supporting and hindering factors, and identify solutions. Design/Methodology/Approach - Data collection employed triangulation techniques, including observation, documentation, and interviews with school administrators, curriculum officials, scout mentors, and students. Data analysis utilized presentation, selection, and analysis techniques. Findings - The results show that Islamic moderation values (Wasathiyah) are implemented through various methods: lectures, role-modeling, habituation, counseling, rewards, and punishment. Patriotic and disciplinary activities include morning assemblies, prayer sessions, Quran recitation, national anthem singing, and Pancasila recitation. Originality/Value - Supporting factors include adequate school facilities, collaborative relationships among teachers, parents, community members, and students, as well as institutional support for scout activities, fostering discipline and patriotism among students.